A European monitoring protocol for the stag beetle, a saproxylic flagship species. Issue 6 (11th September 2016) - Campanaro, Alessandro; Zapponi, Livia; Hardersen, Sönke; Méndez, Marcos; Al Fulaij, Nida; Audisio, Paolo; Bardiani, Marco; Carpaneto, Giuseppe M.; Corezzola, Serena; Della Rocca, Francesca; Harvey, Deborah; Hawes, Colin; et al.
Abstract: Developing protocols for threatened invertebrates is often challenging, because they are not only rare but also elusive. This is the case with the stag beetle ( Lucanus cervus ), a protected and flagship species for the saproxylic beetle fauna in Europe. We applied a standard transect walk at a European scale (8 countries, 29 transects) to test its practicability and reliability as survey design. A total of 533 sightings were recorded throughout the sampling period, but detection probability changed as the season progressed. Considering the observed activity pattern, occupancy models showed that a short period of three consecutive weeks, between the middle of June and the first week of July, resulted in a high probability of detection ( P  >   0.7). As time of the peak of activity varies from year to year and between sites, we propose to extend the sampling period to five weekly surveys. Detailed information on the transect characteristics and the optimal time for surveying were analysed. The data indicate that a weekly transect at dusk provides a reliable method for monitoring this species throughout its distributional range. No correlation was found between latitude, longitude and phenology of sightings, however. However, a standard method such as the one presented, allows broadening the scale of monitoring studies, provinding data to evaluate the efficacy of conservation measures.